Dietary exposure to essential oils of selected Pinus and Abies species leads to morphological changes in Drosophila melanogaster wings - Cvetković, Vladimir J.; Lazarević, Maja; Mitić, Zorica S.; Zlatković, Bojan; Stojković Piperac, Milica; Jevtović, Snežana; Stojanović, Gordana; Žikić, Vladimir (Archives of Biological Sciences, 2024)
Paper description: Essential oils (EOs) are potential sources of biopesticides against pest insects. Since pest activity can rely on flying, the impact of EOs on wing morphology may be important. Wings of Drosophila that were treated at larval stage with selected Pinus and Abies EOs at 3% concentration, were analyzed using geometric morphometrics. Selected Abies and Pinus EOs induced pronounced changes in wing morphology that can be correlated with the toxicity and chemical compositions of the EOs. The tested Abies and Pinus EOs exhibit the potential for use as biopesticides controlling pest activities that depend on insect wing morphology. Abstract: Essential oils (EOs) from conifer species are a potential source of biopesticides due to their various bioactive effects against pest insects. Since the harmful activity of pest insects often relies on their ability to fly, the disruption of wing morphology due to the use of essential oils (EOs) could be significant. This study investigated changes in wing shape and size in the model insect Drosophila melanogaster after exposure to EOs derived from selected conifers species. Drosophila larvae were treated with a diet containing 3% EOs from 6 Pinus and 3 Abies species. After completing their life cycle, the wings of adults were dissected and analyzed using the geometric morphometrics method. Changes in Drosophila wing morphology were observed. The potential effect of the major compounds of the tested EOs on wing morphology is discussed. We believe that this study lays the foundation for further evaluation of Abies and Pinus EOs in targeted toxicological studies against pest insects by focusing on the potential of EOs to disrupt pest activities that depend on wing morphology.